Wigner–Eisenbud–Smith photoionization time delay due to autoioinization resonances. (5th March 2018) - Deshmukh, P C; Kumar, A; Varma, H R; Banerjee, S; Manson, Steven T; Dolmatov, V K; Kheifets, A S
Abstract: An empirical ansatz for the complex photoionization amplitude and Wigner–Eisenbud–Smith time delay in the vicinity of a Fano autoionization resonance are proposed to evaluate and interpret the time delay in the resonant region. The utility of this expression is evaluated in comparison with accurate numerical calculations employing the ab initio relativistic random phase approximation and relativistic multichannel quantum defect theory. The indisputably good qualitative agreement (and semiquantitative agreement) between corresponding results of the proposed model and results produced by the ab initio theories proves the usability of the model. In addition, the phenomenology of the time delay in the vicinity of multichannel autoionizing resonances is detailed.